Interpreting Plant Responses to Clinostating: I. MECHANICAL STRESSES AND ETHYLENE - Salisbury, Frank B. (1981)
The severe epinasty and other symptoms developed by clinostated leafy plants could be responses to gravity compensation and/or the mechanical stresses of leaf flopping. Epinasty in cocklebur (Xanthium strumarium L.), tomato (Lycopersicon esculentum Mill.), and castor bean (Ricinus communis L.) is delayed by inhibitors of ethylene synthesis and action (aminoethoxyvinylglycine and Ag(+)), confirming the role of ethylene in clinostat epinasty. To test the possibility that clinostat mechanical stresses (leaf flopping) cause ethylene production and, thus, epinasty, vertical plants were stressed with constant, gentle, horizontal, or vertical shaking or with a quick, back-and-forth rotation (twisting). Clinostat leaf flopping was closely approximated but with a minimum of gravity compensation, by turning plants so their stems were horizontal, rotating them quickly about the stem axis, and then returning them to the vertical, repeating the treatment every four minutes (clinostat rotation time). None of these mechanical stresses produced significant epinasties, but vigorous hand-shaking (120 seconds per day) generated minor epinasties, as did Ag(+) applied daily (concentrations high enough to cause leaf browning). Plants gently inverted every 20 minutes developed epinasty at about the same rate and to about the same extent as clinostated plants, but plants inverted every 20 minutes and immediately returned to the upright position did not become epinastic. It is concluded that clinostat epinasty is probably caused by disturbances in the gravity perception mechanism, rather than by leaf flopping.